Assessing the Impact of Instructional Materials on Students' Academic Performance in Chemistry: A Study of Secondary Schools in Apa LGA, Benue State - Ijwo, Omirenyi Peter; Ogunwole, Adeshewa Titilayo (Researchparks Publishing, 2025)
The quality and availability of learning materials can make a big difference in how well students perform, especially in subjects like Chemistry. This study looks at how access to instructional resources affects students' academic success in Chemistry across selected secondary schools in Apa Local Government Area, Benue State. Using a mix of surveys and interviews, data were gathered from both students and teachers to assess whether materials like textbooks, laboratory equipment, and Learning materials were sufficient and accessible. The findings suggest that students tend to perform better when they have the right resources, highlighting the need for better-equipped labs, more textbooks, and improved instructional materials. Based on these insights, the study suggests increased investment in educational resources to support better learning and academic achievement in Chemistry.